Perancangan Web Blogger Untuk Meningkatkan Penjualan Online Hijab: Studi Kasus Usaha Hijab YBRA di Jakarta - M. Farhan Ramadhan; Raisra Abrar (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
YBRA Hijab.id MSME is a local fashion business specializing in modern and modest hijab products. As a developing enterprise in the regional market, YBRA Hijab.id faces challenges in expanding its market reach, strengthening its brand identity, and increasing competitiveness. This community service program aims to enhance branding and digital marketing through training and mentoring in promotional strategy development. The methods applied include observation, interviews, training on the use of social media platforms, and implementation of digital content design. The results show an improvement in the MSME’s understanding of branding strategies, digital platform utilization (Instagram, Facebook, TikTok), and consumer engagement. Therefore, empowering YBRA Hijab.id through digital marketing strategies has proven effective in improving the competitiveness and visibility of local fashion businesses.